2022
DOI: 10.1155/2022/6600944
|View full text |Cite
|
Sign up to set email alerts
|

Association of p53 with Neurodegeneration in Parkinson’s Disease

Abstract: p53 is a vital transcriptional protein implicated in regulating diverse cellular processes, including cell cycle arrest, DNA repair, mitochondrial metabolism, redox homeostasis, autophagy, senescence, and apoptosis. Recent studies have revealed that p53 levels and activity are substantially increased in affected neurons in cellular and animal models of Parkinson’s disease (PD) as well as in the brains of PD patients. p53 activation in response to neurodegenerative stress is closely associated with the degenera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 127 publications
0
12
0
Order By: Relevance
“…It was well known that p53 was essential for inducing apoptosis and was responsible for diverse cellular stresses. Pathogenic p53 integrated the cellular stresses comprising the generation ROS, inflammation, abnormal protein accumulation and Ca 2+ overloading, to trigger cell death [42][43][44]. Recent study demonstrated that the specific deletion of p53 gene could eliminate dopaminergic neuronal cell death and further decrease motor deficits in MPTP-treated mice [45].…”
Section: Discussionmentioning
confidence: 99%
“…It was well known that p53 was essential for inducing apoptosis and was responsible for diverse cellular stresses. Pathogenic p53 integrated the cellular stresses comprising the generation ROS, inflammation, abnormal protein accumulation and Ca 2+ overloading, to trigger cell death [42][43][44]. Recent study demonstrated that the specific deletion of p53 gene could eliminate dopaminergic neuronal cell death and further decrease motor deficits in MPTP-treated mice [45].…”
Section: Discussionmentioning
confidence: 99%
“…For example, upregulation of DNA damage and p53, a powerful pro-apoptotic factor, has been reported in a MPTP-induced mouse model, and p53 inhibition can prevent neurodegeneration and ameliorate motor deficits [ 148 , 149 ]. Similarly, DNA damage and apoptotic phenotypes have been observed in other PD toxin models, as well as transgenic mouse models of PD, although p53 may not always be the mediator of cell death in these paradigms [ 29 , 147 , 150 , 151 , 152 ].…”
Section: Mechanisms Of Dna Damage-mediated Neurotoxicity In Pdmentioning
confidence: 91%
“…These factors then facilitate the execution of apoptosis in a caspase-dependent or caspase-independent manner [ 144 , 145 ]. In the context of PD, there is abundant evidence from both patients and experimental models supporting the role of DNA damage-triggered intrinsic apoptotic pathways in DA neurodegeneration [ 146 , 147 ]. For example, upregulation of DNA damage and p53, a powerful pro-apoptotic factor, has been reported in a MPTP-induced mouse model, and p53 inhibition can prevent neurodegeneration and ameliorate motor deficits [ 148 , 149 ].…”
Section: Mechanisms Of Dna Damage-mediated Neurotoxicity In Pdmentioning
confidence: 99%
“…This complexity might be related to the cross-regulation between ISG15 and key tumor suppressors. One of the few identified and validated ISG15 substrates is the tumor suppressor p53, a pivotal transcription factor that coordinates the expression of many DDR effector genes that induce cell-cycle arrest, DNA repair, autophagy, senescence, and apoptosis ( Sandy et al, 2020 ; Luo et al, 2022 ). ISG15 and p53 modulate each other at several levels.…”
Section: Isg15 In the Age-associated Dna Damage Response (Ddr): P53 A...mentioning
confidence: 99%